2011
DOI: 10.5539/gjhs.v4n1p140
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Capabilities of Staphylococcus Aureus and Pseudomonas Aeruginosa Isolated from Tears of HIV/AIDS Patients to Soft Contact Lenses

Abstract: Fifty conjunctival swab samples collected from ELISA confirmed HIV/AIDS seropositive patients who were referred to the HIV/AIDS laboratories of the University of Benin Teaching Hospital and Central Hospital both based in Benin City, Nigeria were aseptically cultured on appropriate media by standard methods. The resulting isolates/strains, after identification by standard methods, were tested for their ability to adhere to two hydrophobic non-ionic daily wear silicone hydrogel soft contact lenses (i.e. lotrafil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…In biological systems, hydrophobic interactions are the strongest long-range non-covalent interactions and are considered a determining factor in microbial adhesion to surfaces ( Sanin et al 2003 ). Given the hydrophobic nature of the surfaces tested in the present study, the results obtained are in agreement with previous works, which show that S. aureus and P. aeruginosa preferentially colonize hydrophobic surfaces than hydrophilic ones ( Ajayi et al 2010 ; Zmantar et al 2011 ). On the other hand, previous studies performed with the same SH surface used in the present work had demonstrated that almost no animal cell adhesion occurred ( Alves et al 2009 ; Song et al 2009 ).…”
Section: Discussionsupporting
confidence: 93%
“…In biological systems, hydrophobic interactions are the strongest long-range non-covalent interactions and are considered a determining factor in microbial adhesion to surfaces ( Sanin et al 2003 ). Given the hydrophobic nature of the surfaces tested in the present study, the results obtained are in agreement with previous works, which show that S. aureus and P. aeruginosa preferentially colonize hydrophobic surfaces than hydrophilic ones ( Ajayi et al 2010 ; Zmantar et al 2011 ). On the other hand, previous studies performed with the same SH surface used in the present work had demonstrated that almost no animal cell adhesion occurred ( Alves et al 2009 ; Song et al 2009 ).…”
Section: Discussionsupporting
confidence: 93%
“…Both Polymacon and Etafilcon-A are materials used in hydrogel contact lenses, but Polymacon is hydrophobic, while Etafilcon-A has hydrophilic properties [ 27 , 28 ]. Water contents of Etafilcon-A and Polymacon are 58% and 38.6%, respectively [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher water content and electrical repulsion might cause albumin to either penetrate into the matrix or repel away from the surface, resulting in less albumin on the surface of Etafilcon-A lenses to undergo conformational changes, resulting in a lower COF (Figure 5d). Both Polymacon and Etafilcon-A are materials used in hydrogel contact lenses, but Polymacon is hydrophobic, while Etafilcon-A has hydrophilic properties [27,28]. Water contents of Etafilcon-A and Polymacon are 58% and 38.6%, respectively [29].…”
Section: Discussionmentioning
confidence: 99%